ALIANSI STRATEGI PROMOSI INDUSTRI PELANCONGAN ANTARA INDONESIA-MALAYSIA - Jaya Atmaja, Edi Jajang (LPPM UBB, 2014)
The effort for a stronger of tourism sectors between Indonesia-Malaysia will be implemented if both country made the promotion partnership in tourism. This partnership is possibly to do between Indonesia-Malaysia because cultural and products similarities, many of tourist comes from intra-ASEAN. Indonesia-Malaysia extend in Malay Archipelago, from the cultural and geografics aspect endow of such uniquely of the tourism products, thatâs make support each others whereas in one management (promotion) together. For this century, the tourists tend for journey and visiting more than one destination. Accross this partnership promotion, the tourism operator of two countries are also give some accommodation in transportation fares such as air, land,and sea transportations, hotels fares, tours, MICE (meeting, incentive, conference and exhibition), cruices and promotions by media. It is done by tourism product so that for the competitiveness quality product improved. Malaysia has 32 offices branch in overseas, and the smoothly for the tourism product of two countries. This promotion cooperation mandatory under Asia Tourism Forum (ATF) in Hanoi, July 2007. The official promotion actually agree between the Ministryof Tourism of Malaysia and Indonesia, this is not implement yet. The two of Ministry designed magazine and video inflight in planes, and they used for tourism product between Indonesia-Malaysia: Two Country, One Destination.Keywords: Alliancy, strategy, promotion, tourism, intra-ASEAN, Malaysia, Indonesia, Malay Archipelago, partnership promotion, MICE, two countries.